Experimental studies and thermodynamic modeling of the carbonation of Portland cement, metakaolin and limestone mortars. (October 2016) - Shi, Zhenguo; Lothenbach, Barbara; Geiker, Mette Rica; Kaufmann, Josef; Leemann, Andreas; Ferreiro, Sergio; Skibsted, Jørgen
Abstract: The carbonation of Portland cement, metakaolin and limestone mortars has been investigated after hydration for 91 days and exposure to 1% (v/v) CO2 at 20 °C/57% RH for 280 days. The carbonation depths have been measured by phenolphthalein whereas mercury intrusion porosimetry (MIP), TGA and thermodynamic modeling have been used to study pore structure, CO2 binding capacity and phase assemblages. The Portland cement has the highest resistance to carbonation due to its highest CO2 binding capacity. The limestone blend has higher CO2 binding capacity than the metakaolin blends, whereas the better carbonation resistance of the metakaolin blends is related to their finer pore structure and lower total porosity, since the finer pores favor capillary condensation. MIP shows a coarsening of the pore threshold upon carbonation for all mortars. Overall, the CO2 binding capacity, porosity and capillary condensation are found to be the decisive parameters governing the carbonation rate.